The Dark Triad Traits and Suicide Risk in Turkish University Students - Gülçin Güler Öztekin; Hülya Örki; Abdulmohsen Mohammed Abdullah Alkhulayfi; Murat Yıldırım (European Journal of Psychology Open, 2025)
Abstract: Aim: It is important to identify the factors associated with suicide risk. This study examines how depression mediates the relationship between the Dark Triad personality traits and suicide risk. Methods: We collected data from 448 Turkish university students (mean age=21.14 ± 1.97; females 72.8%) using an online survey that included the Dark Triad Dirty Dozen Scale, the Depression, Anxiety, and Stress Scale, and the Suicide Probability Scale. Results: The findings indicated that Machiavellianism, psychopathy, and narcissism positively correlated with depression, low self-perception, anger/impulsivity, hopelessness/loneliness, and suicidal ideation. Depression was more associated with Machiavellianism and psychopathy than with suicide ideation. Depression was found to have a significant positive relationship with suicide probability and acted as a mediator between the Dark Triad personality traits and suicide risk. There were stronger direct pathways from psychopathy to suicide ideation than to impulsivity. Discussion/conclusion: These results suggest that the combination of the Dark Triad traits and depression could increase the probability of suicide. Our study highlights the importance of addressing both Dark Triad traits and psychological distress, such as depression, in efforts to reduce suicide risk among university students.